Study of Epidemiology of Traumatic Brain Injury and Prevalence of Psychiatric Disorders in Traumatic Brain Injury at 3 Months Follow-Up - Dade, Nagendra Babu; Teegala, Ramesh; Medikonda, Meena (Nepal Journal of Neuroscience, 2019)
Traumatic brain injury (TBI) is a major global health problem with an annual incidence of 10million cases globally. Despite the good recovery with modern treatment measures, the cognitive and behavioral deficits give rise to the major morbidity. These deficits amount in failure to return to work and maintain social activities. A prospective clinical study of 187 inpatients with Traumatic Brain Injury was done in Alluri Sitarama Raju Academy of Medical Sciences, Eluru, Andhra Pradesh from August 2015 to August 2017. All patients aged between 15-60years, with normal premorbid personality admitted with traumatic brain injury, were included in the study. Appropriate socio-demographic and clinical data was collected while inpatient, and 3 months post trauma. All the patients were subjected to structured interview using MINI PLUS (English version 5.0.0) for assessment of cognitive and neurobehavioral disorders. The prevalence of cognitive and neurobehavioural disorders following traumatic brain injury in the present study was40.6%.Patients with traumatic brain injury often experience enduring emotional and cognitive consequences; major depressive disorder being the most common, followed by somatoform and anxiety disorders. Treatment of these patients should involve a multidisciplinary approach, with the psychiatrist working in close collaboration with the patient, family, neurologist/neurosurgeon, psychologist and social worker.